Polymer dielectrics exhibiting an anomalously improved dielectric constant simultaneously achieved high energy density and efficiency enabled by CdSe/Cd1−xZnxS quantum dots. Issue 27 (2nd July 2020) - Li, Li; Cheng, Jingsai; Cheng, Yunyun; Han, Ting; Liang, Xiao; Zhao, Yan; Zhao, Guanghui; Dong, Lijie
Abstract : Significantly improved energy density and efficiency are achieved by doping CdSe/Cd1− x Zn x S quantum dots into polymers. Abstract : Flexible dielectric polymers and nanocomposites have attracted intensive attention owing to their high electrical breakdown strength, high power density and excellent cycle reliability which are highly demanded for electrostatic energy-storage systems and devices. However, achieving concurrently high discharged energy density ( U e ) and discharge efficiency ( η ) without impairing polymer-endowed mechanical and processing advantages remains a great challenge. In this work, a strategy of doping diminutive CdSe/Cd1− x Zn x S quantum dots (QDs) with a dual-ligand structure into a polymer is demonstrated, by which high U e and η together with largely enhanced mechanical properties are obtained simultaneously. Contrary to conventional sense, a high dielectric constant ( K, 17.8 at 1 kHz) is obtained by adding less than 1 volume percent of QDs into the polymer while both the polymer and QDs are intrinsically low- K materials (<10 and 6–9, respectively). Meanwhile, the small filling ratio of QDs causes no damage but great improvement in mechanical strength and tenacity of the polymer. The energy loss from carrier conduction is greatly suppressed owing to the confinement effect offered by the dual-ligand structure. Thus, a high η (∼90% and 78.3% at 300 and 531.6 MV m −1, respectively) and high U e (21.4 J cm −3 ) which is 17.92 times that of the commercially available dielectric capacitor, biaxially oriented polypropylene (1.2 J cm −3 at 640 MV m −1 ) are achieved. This strategy opens up a new avenue for high-performance polymer dielectrics and related applications.